Local Wisdom vs. Modernity: Reinforcing the Rights of Indigenous Communities in Sustainable Management of Bunaken National Park - Riyad; Syafa’at, Rachmad; Koeswahyono, Imam; Puspitawati, Dhiana (Scientific Journal of Bielsko-Biala School of Finance and Law, 2024)
This research aims to synchronize the misalignment between local wisdom-based and contemporary management of Bunaken National Park, focusing on strengthening the rights of indigenous peoples in the Bunaken National Park area. This study employs a socio-legal approach, supported by sociology, culture, and tourism studies. The results show that the position of indigenous communities in the management of Bunaken National Park remains marginalized, while they cannot participate in formulating and discussing essential policies related to the management of tourism in Bunaken National Park. Additionally, issues often arise related to conflicts over the use of natural resources. These conflicts are mainly related to the management of specific zones within the national park crucial for the traditional activities of the indigenous communities, such as forest utilization, fishing, or collecting marine products. Therefore, it is necessary to formulate management policies incorporating traditional values without diminishing the international standards of Bunaken National Park’s tourism management. It is hoped that the synchronization of these policies will enhance Bunaken National Park as a Super Priority Tourist Destination in Indonesia.